Paternal parenting behaviour, self-esteem, and psychological health of adolescents in Malaysia - Yahya, Amira Najiha (2015)
Psychological health as one of the most crucial indicators of successful adolescents has received considerable attention in the literature. High prevalence rates of various psychological problems amongst adolescents emphasize the significance of identifying paternal parenting behaviour that may reduce the risk of these problems. However, little attention has been given to how fathers influence their adolescents‟ psychological health, especially in an Asian context. Therefore, the present cross-sectional study was undertaken to provide information on the relationships between Malaysian paternal parenting behaviour (warmth, monitoring, harsh discipline, and indigenous) and adolescents psychological health. Additionally, the study examined the mediating role of self-esteem and moderating roles of sex on these relationships. A total sample of 1000 secondary school adolescents aged between 13 and 16 years (mean = 13.91) was recruited using probability proportional to size (PPS) cluster sampling from four states representing four selected regions in Peninsular Malaysia: Perak (Northern), Terengganu (Eastern), Kuala Lumpur (Central), and Malacca (Southern). Adolescents provided data through self-administered questionnaire that consist a series of measures including Malaysian Parenting Behaviour Inventory (Baharudin, Zulkefly, & Arshat, 2014), General Health Questionnaire (Goldberg, 1978) and Rosenberg‟s Self-Esteem Scale (Rosenberg, 1965). The data were analyzed using structural equation modeling (SEM) via AMOS, based on a hypothesized model examining the direct relationships between paternal parenting behaviour (warmth, monitoring, harsh discipline, and indigenous) and psychological health and its indirect effects through self-esteem. Prior to the structural model testing, all of the study measures were validated using confirmatory factor analysis. The goodness of fit of the hypothesized model to the data was found to be satisfactory. The model showed that paternal harsh discipline was significantly and negatively related to psychological health, whereas paternal warmth, monitoring and indigenous were not found to be significant. It also indicated that with exception to monitoring, there were indirect effects of self-esteem in the relationships between paternal warmth to psychological health, paternal harsh discipline to psychological health, and paternal indigenous to psychological health. Multi-group analyses indicated that the model was unstable across sex. Sex differences emerged in the direct relationship between paternal harsh discipline and psychological health. Results also showed that sex differences exist in the pathways from paternal warmth to psychological health, paternal harsh discipline to psychological health, and paternal indigenous parenting to psychological health. Findings from the present study showed that paternal harsh discipline is the leading contributor of disruptive psychological health among the adolescents. Additionally, the indirect effect findings demonstrated the important role of self-esteem in influencing the associations between paternal warmth, paternal indigenous and harsh discipline on psychological health. The study concludes that harsh discipline is detrimental to adolescents‟ psychological health. Paternal warmth and indigenous together with self-esteem on the other hand, could foster better psychological health in adolescents. The findings imply that adolescents with better psychological health tend to have fathers who practices less harsh discipline, greater warmth and indigenous parenting. Findings from the present study thus contribute to the body of knowledge, most notably on the significance role of fathers and self-esteem in shaping adolescents‟ psychological health.